2022
DOI: 10.1096/fj.202100707r
|View full text |Cite
|
Sign up to set email alerts
|

Time‐restricted feeding during the inactive phase abolishes the daily rhythm in mitochondrial respiration in rat skeletal muscle

Abstract: Shift‐workers show an increased incidence of type 2 diabetes mellitus (T2DM). A possible mechanism is the disruption of the circadian timing of glucose homeostasis. Skeletal muscle mitochondrial function is modulated by the molecular clock. We used time‐restricted feeding (TRF) during the inactive phase to investigate how mistimed feeding affects muscle mitochondrial metabolism. Rats on an ad libitum (AL) diet were compared to those that could eat only during the light (inactive) or dark (active) phase. Mitoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 58 publications
1
14
0
Order By: Relevance
“…Rats fed a normal diet limited to ten hours in the daytime inactive period showed disrupted circadian rhythms in the rate of mitochondrial respiration in skeletal muscle. This mimics the metabolic dysfunction observed in human subjects with type-2 diabetes and in night-shift workers, who have a greatly increased risk of type-2 diabetes [ 61 ]. Therefore, fasting during the active period of the circadian cycle may result in an increased risk of metabolic disease if exercise is not performed or if calories are not restricted during the inactive feeding period.…”
Section: Interventional Strategies To Correct Dysfunctional Mqc and D...mentioning
confidence: 56%
See 1 more Smart Citation
“…Rats fed a normal diet limited to ten hours in the daytime inactive period showed disrupted circadian rhythms in the rate of mitochondrial respiration in skeletal muscle. This mimics the metabolic dysfunction observed in human subjects with type-2 diabetes and in night-shift workers, who have a greatly increased risk of type-2 diabetes [ 61 ]. Therefore, fasting during the active period of the circadian cycle may result in an increased risk of metabolic disease if exercise is not performed or if calories are not restricted during the inactive feeding period.…”
Section: Interventional Strategies To Correct Dysfunctional Mqc and D...mentioning
confidence: 56%
“…Under fasting conditions when glutamate dehydrogenase activity is high, αkg levels rise [ 60 ]. This regulation might be partly responsible for the diurnal fluctuations in skeletal muscle αkg levels [ 61 ]. Supplementing with αkg has been shown to increase the lifespan of C. elegans [ 62 ], Drosophila [ 63 ], and mice [ 64 ], while plasma αkg levels decline substantially with aging in mammals [ 65 ].…”
Section: Interventional Strategies To Correct Dysfunctional Mqc and D...mentioning
confidence: 99%
“…[ 41,178 ] In addition, there is no denying that all three regimens can affect gut microbiome, autophagy, and mitochondrial function. [ 37,70,122,153,186,249,300,334 ]…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…[57,68,69] In line with these effects, TRF plays an important role in maintaining the daily rhythm in muscle mitochondrial respiration, and can reset obesity-induced disruption of the muscle clock and restore muscle function. [66,70] TRF can restore the dysregulated WAT clock caused by constant light exposure, albeit the underlying mechanisms remain unclear. [58] Nevertheless, it has been shown that TRF could affect the circadian rhythms of several regulators crucial for adipose function, including fibroblast growth factor 21 (FGF21), [71] and hormonesensitive lipase (HSL).…”
Section: Time-restricted Feedingmentioning
confidence: 99%
“…The process of mitochondrial biogenesis is generally associated with improved cell health and has been reported in various cell types [ 324 , 325 , 326 ]. Inactive phase feeding in rats leads to an altered regulation of mitochondrial biogenesis [ 327 ]. Dietary interventions such as whole-grain bioactive compounds and various polyphenolic compounds also contribute to mitochondrial biogenesis, mainly via the SIRT- PGC1α pathway [ 328 , 329 , 330 ].…”
Section: Mechanisms Of Chrononutrition In Energy Homeostasis and Obesitymentioning
confidence: 99%